The current status and determinants of perceived ageism among community-dwelling older adults: A cross-sectional, multifactorial analysis - Jinlei Du; Min Wang; Xiaoling Wu; Yulian Wu; Ling Lei; Fang Cao; Chencong Nie (PLoS ONE, 2025)
Objective To investigate the prevalence of perceived ageism among community-dwelling older adults and systematically analyze its determinants, thereby providing a reference for the management of mental health in this population. Methods A cross-sectional survey was conducted from April 15–30, 2025, in 45 communities in Zigong City, Sichuan Province, China. A total of 500 questionnaires were distributed, and 484 valid responses were collected. The survey included a general information questionnaire and the Perceived Ageism Questionnaire (PAQ). LASSO (Least Absolute Shrinkage and Selection Operator) regression and multiple linear regression analyses were used to identify risk factors associated with perceived ageism. Results The mean score on the Perceived Ageism Questionnaire was 16.68 ± 3.70. Multiple linear regression analysis revealed that educational level, vision status, and hearing function were significantly associated with perceived ageism among community-dwelling older adults. Conclusion Perceived ageism among community-dwelling older adults is at a moderate level. Healthcare providers should develop targeted interventions based on these determinants to enhance mental health and well-being in this population.